Numerical analysis of WS2/Si3N4 for improved SPR-based HIV DNA detection - Tene, Talia; Cevallos, Yesenia; Marcatoma Tixi, Jessica Alexandra; Pérez Londo, Natalia Alexandra; Gahramanli, Lala; Vacacela Gomez, Cristian (Frontiers in Bioengineering and Biotechnology, 2025)
Surface-plasmon-resonance (SPR) sensors provide label-free nucleic-acid diagnostics, yet they must detect the sub-nanometre refractive-index changes generated by short HIV-DNA hybridisation. Using a transfer-matrix framework, we design a multilayer architecture that couples a 50 nm silver mirror to the analyte through a 7 nm (10 nm) silicon-nitride spacer capped with a monolayer of WS2. This impedance-matched stack (Sys3) concentrates the evanescent field at the recognition surface while chemically passivating the metal. Numerical screening calibrated with published optical constants predicts an angular sensitivity of 167° RIU−1, a limit of detection of 2.99 × 10−5 RIU and a quality factor of 56.9 RIU−1, outperforming gold-based benchmarks and approaching values reported for more reactive ZnSe buffers. Reversing the dielectric sequence (Sys4) increases sensitivity to 201° RIU−1 but lowers fabrication yield and storage stability, establishing Sys3 as the most scalable option. Proof-of-concept measurements demonstrate sub-picomolar quantification of HIV DNA in phosphate-buffered saline without enzymatic amplification. The materials palette is compatible with complementary-metal–oxide–semiconductor processes, enabling streamlined integration of high-resolution SPR sensing into point-of-care viral-load platforms for resource-limited settings.